Resistance or appropriation?: Uptake of exercise after a nurse-led intervention to promote self-management for osteoarthritis. (March 2022) - Morden, Andrew; Ong, Bie Nio; Jinks, Clare; Healey, Emma; Finney, Andrew; Dziedzic, Krysia S
The philosophical underpinning of trials of complex interventions is critiqued for not taking into account causal mechanisms that influence potential outcomes. In this article, we draw from in-depth interviews (with practice nurses and patients) and observations of practice meetings and consultations to investigate the outcomes of a complex intervention to promote self-management (in particular exercise) for osteoarthritis in primary care settings. We argue that nurses interpreted the intervention as underpinned by the need to educate rather than work with patients, and, drawing from Habermasian theory, we argue that expert medicalised knowledge (system) clashed with lay 'lifeworld' prerogatives in an uneven communicative arena (the consultation). In turn, the advice and instructions given to patients were not always commensurate with their 'lifeworld'. Consequently, patients struggled to embed exercise routines into their daily lives for reasons of unsuitable locality, sense-making that 'home' was an inappropriate place to exercise and using embodied knowledge to test the efficacy of exercise on pain. We conclude by arguing that using Habermasian theory helped to understand reasons why the trial failed to increase exercise levels. Our findings suggest that communication styles influence the outcomes of self-management interventions, reinforce the utility of theoretically informed qualitative research embedded within trials to improve conduct and outcomes and indicate incorporating perspectives from human geography can enhance Habermas-informed research and theorising.